Clinical Experience of Using Nasal Drops Milt and Elimination Therapy with Nasal Spray Pshyk in Children with Acute Rhinosinusitis - Yu.V. Havrylenko (Zaslavsky O.Yu., 2015)
The article deals with the treatment of acute rhinosinusitis in children. Attention is paid to unwarranted use of antibiotics, misuse of vasoconstrictor drops. It is emphasized that broad-spectrum antibiotics in accordance with the recommendations of EPOS 2012 should be administered after the 5th day of the disease or in the presence of severe symptoms. Saline irrigation has the highest level of evidence advisability for the administration from the first day of acute rhinosinusitis. The findings of the clinical study on therapeutic effect and tolerability of nasal drops Milt in combination with nasal spray Pshyk manufactured by Farmak сompany (Ukraine) when treating children with acute rhinosinusitis are presented. It is shown that use of these drugs helps maintain and significantly improve the functional state of the nasal mucosa and mucociliary clearance in children with acute rhinosinusitis as well as quickly and safely reduce the signs of inflammation in the nasal cavity and paranasal sinuses. This makes it possible to avoid invasive treatments not only by reducing the symptoms, but also the provision of pathogenetic therapeutic effect.